EFEKTIFITAS PETA KONSEP DALAM PEMBELAJARAN MATA KULIAH DASAR AKUNTANSI - Fachrurrozie, Fachrurrozie; Wahyuningrum, Indah Fajarini Sri (Dinamika Pendidikan, 2010)
Understanding and learning accounting should be done in a systematic, gradual, perseverant and precision way, because accounting consists of complex concept, analysis and skills. Accounting should be studied systematically because it has the sequential inter-related material i.e. started from the identification of the account name of an existing transaction which can be seen in the transaction, journal, general ledger, balance sheet, adjustment, work sheets, preparation of financial statements, closing entry, posting adjustment and closing journals to ledgers, trial balance after closing, and  ended with the journal inverting. To obtain the optimal learning achievement of accounting, accounting students must study thoroughly about the concepts of accounting, as well as trying to understand the relationships among the concepts of accounting, because accounting concepts are related to each other. This research would test the use of maps concept as an alternative media to learn the basic concepts, especially on accounting classification account. The population was also the subject of this research,  they were the 1st semester students  of S1 Accounting Program, Economics Faculty, UNNES in the academic year of  2010/2011. There were 2 classes, the first class was the control class and second class was the experimental class. The control class used the conventional methods in the learning process on the other hand; the experiment class used maps concept in the learning process. The results showed that in experimental class which used maps concept as the media to learn the accounting classification of accounts proved to be more effective than the control class that did not use maps concept as the media in the learning process.